Biotransformation of cyclocanthogenol by the endophytic fungus Alternaria eureka 1E1BL1. (July 2018) - Ekiz, Güner; Duman, Seda; Bedir, Erdal
Abstract: The microbial transformation of cyclocanthogenol (CCG), Astragalus sp. originated sapogenin, by the endophytic fungus Alternaria eureka 1E1BL1 isolated from Astragalus angustifolius was investigated. Hydroxylation, oxidation, epoxidation, O -methylation, ring-expansion and methyl migration reactions were observed on the triterpenoid skeleton. As a result, eight metabolites were isolated and the structures of the previously undescribed compounds were established by 1-D, 2-D NMR and HR-MS analyses. Graphical abstract: The incubation of cyclocanthogenol (CCG) with the endophytic fungus A. eureka 1E1BL1 afforded seven previously undescribed compounds. Highlights: Microbial transformation of cyclocanthogenol yielded eight metabolites. Endophytic fungus Alternaria eureka 1E1BL1 was used as biocatalyst. Hydroxylation, oxidation, epoxidation, O -methylation, ring-expansion and methyl migration reactions were observed. Microbial hydroxylation of cycloartane nucleus at C-17 and C-22 positions was reported for the first time.